PENGARUH DOSIS LIMBAH CAIR BIOGAS TERNAK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI (Capsicum annuum L.) DI TANAH PODZOLIK MERAH KUNING - Noprayandi Topan; Husna Yett; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of the research is determine the effect and obtain the best dose of liquid waste bioslurry of livestock that can increase the growth and yield of chilli plants (Capsicum annuum L.)in the red-yellow podzolic soil. The research has been conducted experimentally by using a completely randomized design (CRD), which consists of 4 treatments and 6 replications.Each unit consists of 3 plants.The treatments were the dose of liquid waste bioslurry (B):B1 = 250, B2 = 375, B3 = 500 and B4 = 625 ml/plants. Parameters measured were plant height, time of flowering, time of harvesting, fruit length, fruit diameter, fruit number and fruit weight.The result showed that the effect of dose of liquid waste bioslurry of livestock significantlyaffected to the growth and yield of red chilli plants wich the best dose was 500 ml/plant. Keywords : liqud waste bioslurry, chili, red-yellow podzolic soil